Effectiveness of Feed Supplement in the Formation Famine Total Candidates on the Queen Honey Bee (Apis cerana) - Nurjanah, Umi (JURNAL BIOSHELL, 2013)
The colony productivity of honey bees is highly dependent on the productivity of the queen. If the queen is too old and less productive or lost than candidates of queen will be formed. If the condition was occurred on dry season, the colonies can be damaged because lack of protein. Therefore, to fulfilled the nutritional needs the colony is given additional feed soybean meal. The study was conducted at the UP-3 Tretes in April to May 2009. Number of colonies used were 10 colonies (10 stup), which consists of 5 as treatments and 5 colonies as control. The data taken is the number of cells that form the queen candidates and the magnitude of additional feed intake treatment soy flour in the colony. The results of the number of candidates for queen cells formed after T test with a = 0.05 turns out there are difference significantly between the colonies and colonies treated controls (t0 = 3.646; ttable = 2.306). This suggests that the number of cells in the colony queen candidate treatment (8.60 ± 3.78) different significantly from the control colonies (1.58 ± 3). The amount of feed intake apparently varies in each colony. Results of the study also showed that supplemental feeding did not show maximum results in colonies inhabited old worker bees.Keywords: supplementary feed, soybean meal, the cell would be queens, Apis cerana.